2015
DOI: 10.1186/s13071-015-0780-y
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the knowledge about Leishmania species in wild mammals and dogs in the Brazilian savannah

Abstract: BackgroundWild, synanthropic and domestic mammals act as hosts and/or reservoirs of several Leishmania spp. Studies on possible reservoirs of Leishmania in different areas are fundamental to understand host-parasite interactions and develop strategies for the surveillance and control of leishmaniasis. In the present study, we evaluated the Leishmania spp. occurrence in mammals in two conservation units and their surroundings in Brasília, Federal District (FD), Brazil.MethodsSmall mammals were captured in Brasí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
0
19
0
2
Order By: Relevance
“…Our prevalence based on ELISA was higher (23.3%) than previously reported (0% in Brazil and 4.1% in Sudan) and based on IFAT was lower (3.3%) than that of previous reports (27.2% in Tunisia and 51.3% in Brazil). The PCR prevalence was nine of 127 animals (7.1%), which is a low prevalence upon comparing to other studies performed in Brazil (BRANDÃO-FILHO et al, 2003;OLIVEIRA et al, 2005;QUARESMA et al, 2011;LIMA et al, 2013;CARDOSO et al, 2015;FERREIRA et al, 2015), South America (ALEXANDER et al, 1998;LIMA et al, 2002), Iran (AKHAVAN et al, 2010;DAVAMI et al, 2013;MIRZAEI et al, 2014), Saudi Arabia (IBRAHIM et al, 1992), Italy (ZANET et al, 2014), Spain (NAVEA-PÉREZ et al, 2015), and Portugal (HELHAZAR et al, 2013). This low prevalence in PCR could be explained by our use of total blood as sample; most other studies used both blood and tissue (liver, spleen, skin, bone marrow).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our prevalence based on ELISA was higher (23.3%) than previously reported (0% in Brazil and 4.1% in Sudan) and based on IFAT was lower (3.3%) than that of previous reports (27.2% in Tunisia and 51.3% in Brazil). The PCR prevalence was nine of 127 animals (7.1%), which is a low prevalence upon comparing to other studies performed in Brazil (BRANDÃO-FILHO et al, 2003;OLIVEIRA et al, 2005;QUARESMA et al, 2011;LIMA et al, 2013;CARDOSO et al, 2015;FERREIRA et al, 2015), South America (ALEXANDER et al, 1998;LIMA et al, 2002), Iran (AKHAVAN et al, 2010;DAVAMI et al, 2013;MIRZAEI et al, 2014), Saudi Arabia (IBRAHIM et al, 1992), Italy (ZANET et al, 2014), Spain (NAVEA-PÉREZ et al, 2015), and Portugal (HELHAZAR et al, 2013). This low prevalence in PCR could be explained by our use of total blood as sample; most other studies used both blood and tissue (liver, spleen, skin, bone marrow).…”
Section: Discussionmentioning
confidence: 52%
“…Clear expansion of leishmaniosis by L. (L.) amazonensis around the country has been observed over the last decades; according to Câmara-Coelho et al (2011) 8% of American cutaneous leishmaniosis cases in Brazil are caused by the above species. Several recent scientific studies describe this expansion; in terms of hosts, Souza et al (2005), Dorval et al, (2010) and Cardoso et al (2015) reported Felis catus domesticus (domestic cat), Mesocricetus auratus (hamster) and Necromys lasiurus (wild rodent) infection. In terms of geographical distribution, Dorval et al (2006), Marlow et al (2013) and Carvalho et al (2013) reported its detection in Mato Grosso do Sul, Santa Catarina and Rio de Janeiro states, Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…For the two study areas, 19% (3 out 16) of the G. agilis tested positive for Leishmania spp through PCR and sequencing. Although the authors concluded that there were no significant differences in infection rates among the mammal species surveyed, the study highlighted the role of G. agilis, in addition to two rodent species, as hosts of Leishmania spp [64]. Until now there has been only one record of an interaction between a species of Monodelphis and Leishmania sp., which was a natural infection of a M. do-mestica (Gray Short-tailed Opossum) in Brazil (Figure 1).…”
Section: The Genus Gracilinanus (Gracile Mouse Opossums) and Leishmaniamentioning
confidence: 86%
“…The second record was in the federal district of Brasilia during a study in two areas, the Brasília National Park (BNP) and the Contagem Biological Reserve (CBR), which are federal conservation units of different types of habitats including grasslands, cerrado and gallery forests [64] (Table 1). For the two study areas, 19% (3 out 16) of the G. agilis tested positive for Leishmania spp through PCR and sequencing.…”
Section: The Genus Gracilinanus (Gracile Mouse Opossums) and Leishmaniamentioning
confidence: 99%
“…However, the occurrence of trypanosomatids in sand fly species and domestic and wild mammals has yet to be fully investigated in the Cerrado biome, particularly in the Federal District (FD) of Brazil (4) , where autochthonous human cases of visceral and cutaneous leishmaniasis have been recorded (5) (6) . The present study focused on the search for Leishmania and other trypanosomatids in sand fl ies from two localities of FD.…”
mentioning
confidence: 99%